THE HEALTH SUPPLY CHAIN PERFORMANCE MEASUREMENT MODEL CASE STUDY OF PHETCHABURI PROVINCE - Ritmak, ์Nutthawut (Journal of MCU Phetchaburi Review, 2024)
The objectives of this research were 1) to study health performance indicators; Integrated according to the supply chain theoretical framework from international indicators and standards By using the Delphi technique, the sample group represents of 18 medical at the expert level from the government sector, used a online questionnaire as a tool to collect data. The research results were found to consist of 4 dimensions, 6 components, and 32 indicators. Measurement includes the upstream dimension, including resource elements in the provision of public health services. The midstream dimension consists of infectious disease control. and the controlling non-communicable diseases (chronic). The downstream dimension consists of health service standards. and health promotion. The population health dimension includes elements of the health situation. 2) To measure the efficiency of the health supply chain. A case study of Phetchaburi Province was found every dimension of the supply chain and every element has not met the standards set by international organizations notified. It is necessary to improve each element to be efficient. Achieve standards to improve the quality of life of the people, economy and society in the future.